Valores de hemoglobina y hematocrito con medidas antropométricas en pobladores adultos del sector “Liberación Social”, Distrito Víctor Larco – Trujillo, noviembre 2018 - Rodríguez Vidal, Karito Geraldine (2019)
In the present work, the hemoglobin and hematocrit values were determined with anthropometric measurements in adult population of the "Liberación Social" sector, Víctor Larco District, one November 2018. Fifty-three blood samples were used from adults aged 18-85 years. The anthropometric measurements were made using variables: hemoglobin (cyanometahemoglobin method), hematocrit (microcentrifugation) and analyzed with body mass index, age and sex, with prior informed consent. The mean values were hemoglobin 13.23 ± 1.77 g / dL, hematocrit 42.33 ± 5.79%, BMI 25.58 ± 3.79 Kg / m2 and age 55.35 ± 14.58 years. 42.59% are overweight and normal hemoglobin (X2 = 3.5216, P> 0.05), 11.11% (group 41-63 years) have decreased hemoglobin (X2 = 3.9694, P> 0, 05) and 9.26% of men have decreased hemoglobin (X2 = 3.6161, P> 0.05). 27.78% are overweight and normal hematocrit (X2 = 2.1069, P> 0.05), 12.96% (group 41-63 years) have decreased hematocrit (X2 = 4.7233, P> 0.05) ) and 11.11% of women had a decreased hematocrit (X2 = 5.8714, P> 0.05). It is concluded that there is no correlation between Hemoglobin and Hematocrit values according to sex, age and BMI